The Influence of Green Product Knowledge, Consumer Attitude, Consumer Trust on The Decision to Purchase Environmentally Friendly Products - Tirta Surya Dewi; Tri Nur Wahyudi (Yayasan Ilomata, 2026)
Environmental concern increasingly influences consumer choices for personal care products, yet a gap persists between green awareness and real purchasing behavior, especially among Generation Z. This explanatory quantitative study investigates the determinants of green purchase decisions for mercury-free, Centella asiatica–based natural skincare products among Generation Z students in Solo Raya. Using an integrated framework that combines the Theory of Planned Behavior and the Green Trust Model, the study tests whether both models function complementarily in explaining the roles of knowledge, attitudes, and trust in shaping consumer decisions. Data were obtained through an online five-point Likert survey (n = 125, purposive sampling) and analyzed using PLS-SEM (SmartPLS 3.3.2). Findings indicate that Green Product Knowledge has a significant negative effect on purchase intention (β = −0.376), suggesting that greater knowledge may heighten skepticism toward product claims or perceived complexity. Conversely, consumer attitude and consumer trust show positive and significant influences on purchase decisions, with attitude identified as the strongest predictor. This study offers novelty by focusing on the socio-culturally diverse Solo Raya region and by empirically integrating TPB and Green Trust constructs, demonstrating their complementary predictive capability. Theoretically, the results refine assumptions that knowledge automatically increases green buying behavior; practically, they suggest that natural skincare brands should balance factual education with persuasive communication that simplifies product understanding and strengthens brand credibility.